Green Entrepreneurial Orientation and Green Innovation in Small and Medium-Sized Enterprises (SMEs) - Muangmee, Chaiyawit; Dacko-Pikiewicz, Zdzisława; Meekaewkunchorn, Nusanee; Kassakorn, Nuttapon; Khalid, Bilal (Social sciences (Basel), 2021)
Since environmental issues are becoming an integral part of business performances, policymakers and managers have started recognizing the importance of green innovation towards sustainable business performances. The role of the automotive parts industry is crucial in minimizing environmental degradation and promoting sustainable development. Yet few studies have focused on the connection between green entrepreneurial orientation and green innovation that may affect small and medium enterprise (SME) business performance. Therefore, this study aims to analyze the influence of green entrepreneurial orientation on green innovations, and its effects on sustainable business performances in the automotive parts industry in Thailand. The sample consists of 226 SMEs in the automotive parts industry in Thailand. The partial least square method (PLS-SEM) has been used for the analysis of data. The results of the study show that green innovations have the strongest influence on economic and environmental performances. This study contributes to resource-based view theory by incorporating green innovation as a strategic competency of SMEs’ performance. Further, green entrepreneurial orientation and green innovation can assist SME managers in understanding the factors leading to sustainable performance of businesses.